Visualisasi Data Pendidikan SD & SMP Daerah Kabupaten Tangerang Menggunakan Aplikasi Microsoft Power Business Intellegence - Dwi Hermawan, Dicky; Andriansyah, Miftah (Green Publisher Indonesia, 2025)
This research focuses on the visualization of educational data for elementary and junior high schools in Tangerang Regency using the Microsoft Power Business Intelligence (Power BI) application. The purpose of this study is to present education data more effectively and informatively, so that it can support better decision-making by stakeholders. The data used in this study was taken from the Tangerang Regency Opendata portal and BPS Tangerang Regency in the period 2019 to 2021. The method used in this study is the CRISP-DM (Cross-Industry Standard Process for Data Mining) method applied in the research stages which include business understanding, data understanding, data preparation, modeling, evaluation, and deployment. User Acceptance Testing (UAT) testing is used to evaluate the dashboard created. The results from UAT show that the developed dashboard obtained a score of 87,13%, which is included in the